Performance of Helium-Valved Linear Compressor Motor for Space Use - Liu Kangjun; Sha Xinquan; Li Zicheng; Huang Qi; Ying Kongkuai; Ding Lei; Liu Shaoshuai; Jiang Zhenhua; Wu Yinong (Zhileng xuebao)
As the driving component of a valved linear compressor, the matching relationship between the motor force and gas force directly affects the performance of the compressor. A simulation model of the linear motor was established based on the equivalent gas-force model. In addition, a test bench for the valved linear compressor was constructed to analyze both the simulation and experimental results under various working conditions. This study aimed to investigate the performance of a compressor across different operating scenarios while verifying the reliability of gas force linearization. When the inflation pressure and piston pressure were 0.2 MPa and 5 mm, respectively, the resonance frequency of the experiment and simulation was 50 Hz, and the motor efficiency was 84.3%. The maximum relative errors of the input work, voltage, current, and motor efficiency were 25.8%, 21.7%, 22.7%, and 13.5%, respectively. This indicates that the motor efficiency of the compressor is related to its resonance frequency and that the motor efficiency of the compressor is the highest when the resonance frequency is consistent with the operating frequency. The simulation model of the linear motor is reliable, and the calculation results for the gas load are relatively accurate.